HEPATITIS C VIRUS INFECTION IN HEMODIALYSIS PATIENTS: COMPARISON OF THE SURABAYA DIALYSIS CENTER AND JUNTENDO UNIVERSITY HOSPITAL DIALYSIS CENTRE - santoso, djoko; pranawa, pranawa; Yogiantoro, Moh.; Widodo, Widodo; Wardana, Aditia; Mardiana, Nunuk; Mohani, Chandra Irwanadi; soewanto, soewanto; Shou, Ichiyu; Maeda, Kunimi; Hamada, chieko; Fukui, Mitsumine; Horikoshi, Satoshi; Tomino, Yasuhiko (Indonesian Journal of Tropical and Infectious Disease, 2010)
Hepatitis C virus infection is highly prevalence in chronic hemodialysis (HD) patients. The present study will compare prevalence of HCV positive population in difference countries where there are great contrasts in and diversity of care available to patients who have end stage renal disease. All serum samples of the 100 patients were tested for HCV antibodies, using third-generation enzyme immunoassay. The prevalence of anti-HCV was correlated with a history of blood transfusion and with duration of hemodialysis. HCV prevalences were 88% of Surabaya group and 6% of Juntendo Group, respectively. In Surabaya Group, prevalence of HCV positive was high and the risk factors are not only those of the Juntendo Group, but also a combination of poor living conditions, frequent blood transfusions, and lack of adherence. Much needs to be studied about the role of universal screening and effective techniques for primary prevention in Surabaya Group